Loss of cotyledons in different stages in initial bean growth - Lapaz, Allan de Marcos; Melo Santos, Luiz Felipe de [UNESP]; Pereira Yoshida, Camila Hatsu; Monteiro de Figueiredo, Paulo Alexandre [UNESP]; Viana, Ronaldo da Silva [UNESP]; Manzani Lisboa, Lucas Aparecido [UNESP] (Fundacao Zoobotanica Rio Grande Sul, Museu Ciencias Naturais, 2017)
The objective of this work was to analyze the effect of cotyledon loss at different times of initial bean growth. The experimental design was completely randomized in a factorial scheme of 2x5, seedlings with zero and one cotyledon, interacting with five extraction stages: zero, one, two, four, and six days after germination, with five replicates composed of three seedlings. After 15 days, the following parameters were evaluated: mean root and shoot length; mean stem diameter; leaf area; total shoot and root dry mass; phloem and xylem diameter; and thickness of abaxial and adaxial epidermis. Removing cotyledons during the initial development of the bean plant influenced all the parameters evaluated in this work, except the mean diameter of the stem with one cotyledon. The removal of cotyledons in the first days of extractions hinders the initial development of the plant, as well as making it more susceptible to the environment.
Keywords: stress; nutrients; plant morphology; Phaseolus vulgaris L.